2014
DOI: 10.1200/jco.2013.54.5020
|View full text |Cite
|
Sign up to set email alerts
|

Triple Intrathecal Therapy Alone With Omission of Cranial Radiation in Children With Acute Lymphoblastic Leukemia

Abstract: Delaying first TIT until circulating blasts have cleared may improve CNS control in children with newly diagnosed ALL and preclude the need for CrRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 28 publications
2
44
0
1
Order By: Relevance
“…Such a systematic change may have slightly changed the incidence pattern of childhood cancer. Future validation with an external data source, such as a nongovernment organization or a cooperative study group with an independent database [34][35][36], can further help to confirm the incidence-trend of childhood cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a systematic change may have slightly changed the incidence pattern of childhood cancer. Future validation with an external data source, such as a nongovernment organization or a cooperative study group with an independent database [34][35][36], can further help to confirm the incidence-trend of childhood cancers.…”
Section: Discussionmentioning
confidence: 99%
“…cancer risks and treatment outcome, which direct future studies on individual cancer types. Whether new therapeutic regimens improve the patient survival and outcome will be best answered through cooperative clinical protocols [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Two reports have shown that delayed lumbar puncture reduced the iatrogenic invasion of the CNS and contributed to minimize the proportion of cases requiring intensified CNS therapy without compromising the outcome. In the TCCSG trials, the first IT was delayed at day 8, and the Taiwan Pediatric Oncology Group (TPOG) postponed the first IT until the disappearance of blasts from the peripheral blood at day 10 . Optimal timing of the first IT, however, is yet to be determined.…”
Section: Treatmentmentioning
confidence: 99%
“…Recently the complete abandonment of cranial irradiation has been incorporated into frontline trials even for patients with overt CNS disease at diagnosis (47, 48). Pui showed that by augmenting systemic therapy, using triple IT therapy, reducing traumatic lumbar punctures (associated with contamination of the CNS with peripheral blood blasts), and using risk stratified therapy that included minimal residual disease testing achieved a superior 5 year EFS (93.5%) with only 2.7% of patients suffering a CNS relapse (47).…”
Section: Optimizing Cns Therapy To Prevent Neurocognitive Toxicitymentioning
confidence: 99%